The Relationship of Carotid Intima-Media Thickness with Cell Adhesion Molecules and Pentraxin-3 in Patients with Psoriatic Arthritis - Soysal Gündüz, Özgü; Armağan Alptürker, Kezban; Güler Şen, Menice; Can, Fatma; Erdal, Serkan; Ulman, Cevval; Pırıldar, Timur (Aktuelle Rheumatologie, 2022)
Aim Cardiovascular morbidity is increased in patients with psoriatic arthritis (PsA) compared to the general population. Several recent studies have indicated that pentraxin 3 (PTX-3) and cell adhesion molecules (CAMs) might be independent biomarkers of subclinical atherosclerosis. In this study, we aimed to determine the relationship of CAMs and PTX-3 with carotid intima media thickness (CIMT) in patients with PsA and to compare CIMT and serum levels of these biomarkers in patients with healthy controls (HCs).Method PsA patients fulfilling the CASPAR (Classification criteria for Psoriatic Arthritis) criteria without traditional cardiovascular (CV) comorbidity and HCs without autoimmune and/or CV disease were included in this cross-sectional study. Carotid artery Doppler ultrasound examinations were conducted by a single radiologist blinded to the participants’ clinical characteristics. Serum vascular adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1), E-selectin, and PTX-3 concentrations were analized.Results 43 PsA patients (27 females, mean age 42.49±11.70 years, and a mean disease duration of 9.37±7.96 years) and 37 HCs (28 females, mean age 42.16±11.38 years) were included. In regression analyses, age and PTX-3 were found to be the best predictors of CIMT in patients with PsA. CIMT was significantly higher in PsA patients compared with HCs (0.63±0.18 vs. 0.49±0.10 mm, p<0.01). In te PsA group, serum levels of PTX-3, ICAM-1, and VCAM-1 were also significantly higher than HCs. CIMT correlated positively with age, disease duration, PTX-3, ICAM-1, and VCAM-1 (p<0.05).Conclusion In our study, age and serum level of PTX-3 were found to be the predictors of CIMT in patients with PsA without CV comorbidity. This outcome highlights the importance of monitoring CIMT and serum level of PTX-3 as CV risk factors in PsA patients.
Keywords: psoriatic arthritis; aterosclerosis; carotid intima–media thickness; cell adhesion molecules; pentraxin 3